Ambiguity in Blasphemy Law Norms: Challenges to Religious and Expressive Rights in the Digital Age - M Mufidah; H Hartiwiningsih; I Isharyanto (Proceeding International Conference Restructuring and Transforming Law, 2024)
Law No. 1/1965/PNPS on Blasphemy has become a highly sensitive legal framework aimed at safeguarding the harmony of religious freedom in Indonesia. However, in the context of technological advancements and the digital world, this law has undergone significant polarization, particularly in addressing actions deemed as blasphemy on social media. This polarization has consequently restricted the space for religious freedom and freedom of expression. This article analyzes the blasphemy law, which was initially designed to protect religious freedom but has evolved into a controversial regulation characterized by normative ambiguities. Employing statutory, philosophical, and sociological approaches, this study explores the legal objectives linked to the norms within the blasphemy law. Furthermore, it examines the interplay between Indonesia's religious culture and the phenomena of the digital era. Cases involving blasphemy on social media highlight critical issues, including the escalation of controversies, trial by media, selective criminalization, and pressure on freedom of expression. The article concludes that the normative ambiguity of Indonesia's blasphemy law presents significant challenges in upholding guarantees for religious freedom and freedom of expression. These challenges not only create legal uncertainty but also open avenues for political misuse. Therefore, legal reform is urgently required to establish clearer and more robust protections for human rights, particularly the rights to religious freedom and freedom of expression, while ensuring justice and equality for all citizens as mandated by the Constitution.